Resepsi Komodifikasi Halal pada Iklan Jilbab Zoya - Juri Lestari; Kamila Adnani (Academic Journal of Da'wa and Communication, 2020)
Giving halal certification for many products is a guarantee that products is safe for consumption by a Muslim people. But media tend to using religion value to get a big commodity that profitable for company, or change the using value of religion to economic value. This research is a study about audience of television advertisement with the reception approach. This research is for knowing how are the Solo Hijabers community members meaning to Zoya Hijab advertisement. This research is using a qualitative method. Data analysis that using is Reception by Stuart Hall (encoding-decoding) with using three kind of analysis, dominant hegemonic position, negotiated position, and oppositional position. The result that researcher get is just showing two types, that is hegemonic dominant and negotiation. While the opposite position not happen to Hijabers Solo Community. In this research also found interesting something, although informant nothing have an attitude, meaning, and act the same way. They are still agree of hijab Zoya distribution in the market. Even they want to buy or using that hijab. Without they realize, they agree halal value to the Zoya hijab advertisement is a form of commodification.